Treated Greywater as a Novel Water Resource: The Perspective of Greywater Treatment for Reuse from a Bibliometric Analysis - Aguirre-Quintana, M; Aguirre-Quintana, M; Romero-Figueroa, J; Quijada-Maldonado, E; Yanez-Sevilla, D; Abejon-Elias, R (IWA Publishing, 2024)
The current global water crisis has prompted research into technologies that can reuse different water resources to mitigate water scarcity. The use of treated greywater can be proposed to provide additional water resources. By reusing this water in different applications, this water crisis can be mitigated at the local scale. This study presents a bibliometric analysis to assess the state of the art of greywater treatment and its reuse technologies. This analysis is based on the scientific literature published until 2023 in Scopus regarding greywater treatment and 1,024 documents were found. The results showed a clear exponential increase in the accumulated number of publications in this topic, which was spurred during the mid-1990s. The most prolific country was the United States, while China, the other typical scientific superpower in most fields, occupied the sixth position in the ranking. Environmental Sciences was the knowledge subject with more documents, followed by Engineering and Chemical Engineering. The bibliometric study was complemented using SciMAT to create bibliometric networks that represent the dynamic evolution of the themes. The most important themes were identified, among which three key points stand out: greywater characterization, technologies for greywater treatment, and water management, including the reuse of treated greywater. © 2024 The Authors.